3,3 '-Diindolylmethane Supplementation Maintains Oocyte Quality by Reducing Oxidative Stress and CEP-1/p53-Mediated Regulation of Germ Cells in a Reproductively Aged Caenorhabditis elegans Model - Lee Mijin; Youn Esther; Kang Kyungsu; Shim Yhong-Hee (MDPI AG, 2022)
In recent decades, maternal age at first birth has increased, as has the risk of infertility due to rapidly declining oocyte quality with age. Therefore, an understanding of female reproductive aging and the development of potential modulators to control oocyte quality are required. In this study, we investigated the effects of 3,3'-diindolylmethane (DIM), a natural metabolite of indole-3-cabinol found in cruciferous vegetables, on fertility in a Caenorhabditis elegans model. C. elegans fed DIM showed decreased mitochondrial dysfunction, oxidative stress, and chromosomal aberrations in aged oocytes, and thus reduced embryonic lethality, suggesting that DIM, a dietary natural antioxidant, improves oocyte quality. Furthermore, DIM supplementation maintained germ cell apoptosis (GCA) and germ cell proliferation (GCP) in a CEP-1 /p53-dependent manner in a reproductively aged C. elegans germ line. DIM-induced GCA was mediated by the CEP-1-EGL-1 pathway without HUS-1 activation, suggesting that DIM-induced GCA is different from DNA damage-induced GCA in the C. elegans germ line. Taken together, we propose that DIM supplementation delays the onset of reproductive aging by maintaining the levels of GCP and GCA and oocyte quality in a reproductively aged C. elegans.